PEMIKIRAN POLITIK ABDURRAHMAN WAHID TENTANG DEMOKRASI DI INDONESIA - Abdul Muchit Fajar; Hotrun Siregar, MSi. (Jurnal Communitarian (Prodi Ilmu Politik), 2021)
AbstractThis research wants to know how democracy should be applied together with the Indigenousization of Islam in Abdurrahman Wahid's view. From this research, it is known that the constitutionalization of democracy through efforts to realize the rule of law is the main prerequisite for democracy. The Pancasila democracy that was initiated by the New Order was simply described by Abdurrahman Wahid as a "as it were democracy". It’s as if it’s democracy, even though in it all components of democracy are blocked. The New Order made Pancasila as an apologetic ideology to wrap up the practice of tyrannical power with Pancasila democratic values to give birth to interpretive authoritarianism which then made Pancasila the absolute property of the government, and democracy also transformed into procedural formalism that led to one ruler. From this space, Abdurrahman Wahid's idea of democracy was born. As the antithesis of the Pancasila democracy of the New Order which he was concerned about. For him, democracy which only rests on institutionalization; trias politica, elections, Komnas HAM and so on have not been able to guarantee the fulfillment of a sense of justice, equality of rights and freedom. Another important element which is a pillar of democracy for him is the importance of upholding human rights, improving people's welfare, respecting plurality and empowering civil society. These five things are what we must ultimately strive for consistently for the realization of justice, equality of rights and freedoms as stated in the 1945 Constitution.AbstrakPenelitian ini ingin mengetahui bagaimana seharusnya Demokrasi diaplikasikan bersamaan dengan Pribumisasi Islam dalam pandangan Abdurrahman Wahid. Dari penelitian ini kemudian diketahui bahwa konstitusionalisasi demokrasi melalui upaya mewujudkan kedaulatan hukum merupakan prasyarat utama bagi demokrasi. Demokrasi Pancasila yang digulirkan Orde Baru secara sederhana digambarkan Abdurrahman Wahid sebagai “Demokrasi seolah-olah”. Seolah-olah demokrasi padahal di dalamnya semua komponen demokrasi dibendung. Orde Baru telah menjadikan Pancasila sebagai ideologi apologetik untuk membungkus praktik kekuasaan tiranik dengan nilai-nilai demokrasi yang Pancasilais hingga melahirkan Otoritarianisme penafsiran yang kemudian menjadikan Pancasila sebagai milik mutlak dari pemerintah, dan demokrasipun menjelma formalisme prosedural yang berujung kepada satu penguasa. Dari ruang inilah gagasan demokrasi Abdurrahman Wahid lahir. Sebagai antitesa dari demokrasi Pancasila Orde Baru yang secara concern beliau perjuangkan. Baginya, demokrasi yang hanya bertumpu pada institusionalisasi; trias politica, pemilu, Komnas HAM dan seterusnya belum bisa menjamin terpenuhinya rasa keadilan, persamaan hak serta kebebasan. Elemen penting lainnya yang merupakan pilar demokrasi baginya adalah pentingnya penegakan Hak Asasi Manusia, peningkatan kesejahteraan rakyat, penghargaan terhadap pluralitas dan pemberdayaan masyarakat sipil. Kelima hal inilah yang pada akhirnya harus kita perjuangkan secara konsisten demi terwujudnya keadilan, persamaan hak dan kebebasan sebagaimana tertuang dalam Undang-undang Dasar 1945.Keywords: Demokrasi, Pribumisasi Islam, Abdurrahman Wahid